Development and Implementation of an Innovation Strategy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
An innovation strategy is essential for organizations looking to maintain a competitive edge, drive growth, and ensure long-term success in today’s dynamic business environment. The paper presents the essence of innovation strategy, discusses the features and significance of innovation strategy for companies. Moreover, the article displays the main stages of the formation of an innovation strategy and substantiates with examples the effectiveness of applying an innovation strategy in the activities of companies.